Deciphering bacterial community succession patterns and their correlations with physicochemical factors in solid-state fermentation of high-quality jujube vinegar - FAN,Ying (2022)
Abstract Liquid-state fermentation (LSF) with purified microbial strains is predominantly used to produce fruit vinegar, resulting in a bland flavor, poor aroma, and pungent sour aftertaste. Herein, jujube vinegar was produced using the solid-state fermentation (SSF) technology. The results showed that the concentrations of non-volatile acids, total esters, proteins, free amino acids, reducing sugars, and total flavonoids in jujube vinegar produced by SSF (SSFJV) were higher than those in jujube vinegar produced by LSF (LSFJV). Fuzzy mathematical sensory evaluation results showed that SSFJV had ‘excellent’ sensory quality, while LSFJV was of ‘medium’ quality. High-throughput sequencing identified various bacteria involved in the SSF process. Based on bacterial community succession, the SSF process can be divided into four stages, with Staphylococcus, Pediococcus, Lactobacillus, and Acetobacter as the dominant genera, respectively. Spearman’s correlation analyses indicated that specific functional bacteria exhibited positive effects on the levels of non-volatile acids, total esters, proteins, free amino acids, and titratable acidity in the fermentation substrate. The results provide insight into the microbial mechanisms underpinning quality improvement of fruit vinegar by SSF, and support for artificial construction of functional bacterial agents suitable for fruit vinegar brewing.